2009
DOI: 10.1051/0004-6361/200912289
|View full text |Cite
|
Sign up to set email alerts
|

6Li/7Li estimates for metal-poor stars

Abstract: Context. The presence of the lithium-6 isotope in some metal-poor stars is a matter of surprise because of the high values observed. Non-standard models of Big Bang nucleosynthesis and pre-Galactic cosmic ray fusion and spallation have been proposed to explain these values. However, the observations of this light isotope are challenging which may make some detections disputable. Aims. The goal was to determine 6 Li/ 7 Li for a sample of metal-poor stars; three of them have been previously studied and the remai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Synthetic barium profiles were, like the iron profiles, the result of an interpolation of profiles synthesised The isotope ratio was determined with a χ 2 routine modified from that of García Pérez et al (2009), which fits synthetic barium profiles with varying barium abundance and isotope configuration. The wavelength shift is also measured by shifting the observed profile so that the best fit can be attained, through the χ 2 minimum.…”
Section: Barium Isotope Ratiomentioning
confidence: 99%
“…Synthetic barium profiles were, like the iron profiles, the result of an interpolation of profiles synthesised The isotope ratio was determined with a χ 2 routine modified from that of García Pérez et al (2009), which fits synthetic barium profiles with varying barium abundance and isotope configuration. The wavelength shift is also measured by shifting the observed profile so that the best fit can be attained, through the χ 2 minimum.…”
Section: Barium Isotope Ratiomentioning
confidence: 99%
“…To recap on Gallagher et al (2010), we use a χ 2 code (derived from that of García Pérez et al 2009) to compare the observed and synthetic spectra of a number of Fe i and Fe ii lines, computed for different abundances A(Fe) 3 , wavelength shifts Δλ, and line broadening parameters. Two different broadening approaches are used, as described below.…”
Section: Determination Of the Macroturbulencementioning
confidence: 99%
“…In addition, one has to be very careful with the flat-fielding and rectification of the spectra to ensure that the continuum near the Li i 6708Å line is accurate to better than 0.2 %. In this connection, it was mentioned that the non-detection of 6 Li in G 64-37 ( 6 Li/ 7 Li = 0.01 ± 0.04) by García Pérez et al (2009) (in contrast to the 3-sigma detection by Asplund & Meléndez quoted above) may be due to problems with residual fringes after flat-fielding of the Subaru/HDS spectra, as also discussed by García Pérez et al themselves.…”
Section: P E Nissenmentioning
confidence: 78%